Pru and the Fomorian giants - Cullum, Jared; Henson, Jim (Archaia, a division of Boom Entertainment, Inc., 2017)
Jim Henson's The Storyteller: Giants is a collection of mythic tales of when giants roamed the Earth, inspired by folklore from around the world and told in the spirit of Jim Henson's beloved television series. In this third issue, when Pru's little brother Spoon goes missing, she'll need the help of a forest spirit to save him from the lair of Ireland's most fabled supernatural beings: the Fomorian Giants. Presented by Jared Cullum in gorgeous watercolor.